Going green Who is investing in energy efficiency, and why it matters - European Investment Bank (European Investment Bank, 2020)
Investments in energy efficiency improvements are vital to ensure Europe's future as a sustainable, yet prosperous economy. Amid the COVID-19 crisis, however, there is a great risk of losing sight of the benefits of energy efficiency investments by European firms. The EIB Investment Survey (EIBIS) provides a unique source of data that highlights how more investment in energy efficiency is needed. This report examines the quality of firms' building stock, their spending on energy efficiency measures and the factors that influence their decisions regarding that investment. It highlights that both high-quality information and advanced management practices make a crucial difference in the likelihood of investment in energy efficiency. The regulatory framework needs to be supportive, yet also push for higher energy building performance standards, while financing conditions should facilitate timely investment by firms to realise the enormous gains that can be achieved through energy efficiency improvements.